Analisis Penerapan Metode 5s+Safety Pada Gudang Pusat PT. X - Ahmad Farhan Hafiduddin; Nur Rahmawati (Ocean Engineering : Jurnal Ilmu Teknik dan Teknologi Maritim, 2023)
Central warehouse PT. X is a place to store materials needed for production. PT. X is a large company operating in the maritime and energy sectors. 5S work culture (Seiri, Seiton, Seiso, Seikatsu, Shitsuke) is a work culture adopted from Japan which aims to create an orderly work environment and increase safety, efficiency and reduce non-value added activities. The implementation of the 5S+Safety culture is implemented according to the SOPs in the central warehouse, but the implementation is not optimal. Implementation of the 5S+Safety method in the PT warehouse. X is considered not optimal because only 2S (Seiketsu and Shitsuke) is running well while 4S (Seiri, Seiton, Seiso, Safety) is not running well. Warehouse employees are advised to apply the 5R checklist and carry out routine independent audits which will be supervised by the department head. Therefore, this research was conducted to evaluate the implementation of 5S+Safety in PT. X’s central warehouse. Evaluation results using the 5S+Safety method support increasing company productivity and performance.